Intravitreal Dexamethasone for the Treatment of CMO Associated with Refractory Sclerouveitis. (2nd January 2018) - Pohlmann, Dominika; Winterhalter, Sibylle; Pleyer, Uwe
ABSTRACT: Purpose : To assess the efficacy and tolerability of intravitreal dexamethasone 0.7 mg sustained-release insert (Ozurdex ® ) in patients with sclerouveitis and recurrent cystoid macula edema (CMO) refractory to treatment. Methods : Interventional retrospective case series of five patients receiving 13 intravitreal dexamethasone inserts. Results : Three of five patients presented with an associated systemic disorder, whereas two patients had idiopathic sclerouveitis. All patients received immunosuppressive therapy. The CRT mean (SD) decreased in all eyes from 428 μm (137) (baseline) to 327 μm (149) (1 month), 342 μm (155) (3 months), 297 μm (99) (6 months) and reduced scleral inflammation. No morphologic adverse changes were noted, in particular, no scleral melting or necrosis occurred. Conclusions : Intravitreal dexamethasone may be an effective and safe therapeutic option in sclerouveitis with otherwise treatment-resistant CMO. It resolves not only CMO, but also provides a reduction of scleral inflammation and ocular pain. Nonetheless, adequate immunosuppressive treatment of an underlying disease must ensue.